Dramatic interactions : teaching languages, literatures, and cultures through theater : theoretical approaches and classroom practices - Ryan-Scheutz, Colleen; Marini-Maio, Nicoletta, 1961- (Cambridge Scholars, 2011)
"Dramatic Interactions is a collection of essays on the flourishing and interdisciplinary subject of teaching foreign languages, literatures, and cultures through theater. With rich examples from a variety of commonly and less commonly taught languages, this book affirms both the relevance and effectiveness of using theater for foreign language learning in the most comprehensive sense of the term. It includes innovative approaches to specific theatrical texts and addresses numerous aspects of foreign language learning such as oral proficiency and communication, intercultural competence, the role of affect and motivation in foreign language study, multiple literacies, regional variations and dialect, literary analysis and adaptation, and the overall liberating effects of verbal and non-verbal self-expression in the foreign language. Dramatic Interactions renders accessible, efficacious, and enjoyable the study of languages, literatures, and cultures through theater with the hope of inspiring and facilitating the greater incorporation of theatrical texts and techniques in foreign language courses at every level."--Page [4] of jacket.